Appropriate intradeltoid muscle needle penetration depth in vaccine administration: an MRI study in Thailand - Laohawiriyakamol, Teeranan; Boonsri, Pattira; Phutphithak, Khetnathee; Niyomkarn, Thamonchanok; Klabklay, Prapakorn; Chuaychoosakoon, Chaiwat (Frontiers in Immunology, 2023)
The objective of this study was to evaluate the appropriate vaccination needle penetration depth into the deltoid muscle to avoid injection-site complications from an inappropriate injection depth and/or injection site.This was a retrospective study using axial proton density-weighted images of MRI shoulders at the level of 2 fingerbreadths below the acromion process to measure the combined thickness of the skin, subcutaneous tissue and deltoid muscle to evaluate the percentage of injections into the deltoid muscle with various needle penetration depths.Results: There were 509 MRI shoulder images of 222 males and 287 females (265 of right shoulders and 244 of left shoulders). The average BMI and age were 24.54 ± 3.54 kg/m 2 and 64.81 ± 10.20 years, respectively. Using a needle penetration depth of 12.7 mm (0.5 inches) achieved 100% of injections into the deltoid muscle.We recommend advancing the entire length of a 0.5-inch needle perpendicular to the skin at 2 fingerbreadths below the acromion process for adult intradeltoid vaccinations. This approach ensures optimal vaccine delivery and minimizes the risk of injection-related injuries.